Protection behavior of fluorine-containing cover gases on molten magnesium alloys - 熊守美 王先飞 (Transactions of Nonferrous Metals Society of China, 2010)
The sulphur hexa-fluoride gas（SF6）, which is commonly used as the cover gas of molten magnesium alloys in the magnesium industry today, has an extremely high global warming potential（GWP）. The protection mechanism of SF6 containing cover gases on molten magnesium alloys was presented. The cover gas protects the melt by reacting with the melt to form a coherent protective film on the melt surface. The film contains MgO and MgF2. Particles containing MgF2 form on the interface between the oxide film and the bulk magnesium alloy, which correspond to the concave areas from the surface observation. These particles increase the Pilling and Bedworth ratio of surface film and enhance the protective capability of the films. Based on the understanding of the mechanism of SF6, a melting technology in a sealed furnace was proposed, and the protection behavior of magnesium alloys in the sealed melting furnace was investigated under the protective atmosphere containing HFC-134a. The morphology and composition of the surface film were also studied. Experiments to evaluate the protective effect of two other fluorine containing gases with low GWPs on AZglD alloy in the sealed furnace were also carried out, and the results show that the new gases are potential substitutes for SF6.